Anti-diabetic, anti-oxidant and anti-hyperlipidemic activities of Melastoma malabathricum Linn. leaves in streptozotocin induced diabetic rats - Kumar, Vikas (BioMed Central, 2013)
BACKGROUND: Melastoma malabathricum (MM) Linn leaves traditionally use in the treatment of diabetic conditions. The aim of the present investigation was to evaluate the antioxidant, antihyperlipidemic and antidiabetic activity of methanolic extract taken from Melastoma malabathricum Linn (Melastomaceae). METHODS: The methanolic leaves extract of MM Linn leaves used for the study. Chemical test of different extract, acute toxicity study and oral glucose test was performed. Diabetes was induced in rat by single intra-peritoneal injection of streptozotocin (55 mg/kg). The rats were divided into following groups: Group I – normal control, Group II (Vehicle) – diabetic control, Group III (STZ-toxic) – MM I (100 mg/kg, p.o.), Group IV – MM II (250 mg/kg, p.o.), Group V – MM III (500 mg/kg, p.o.), Group VI – glibenclamide (10 mg/kg, p.o.). Bodyweight of each rat in the different groups was recorded daily. Biochemical and antioxidant enzyme parameters were determined on day 28. Histology of different organ (heart, liver, kidney, and pancreas) was performed after sacrificing the rats with euthanasia. RESULTS: The methanolic extract of MM did not show any acute toxicity up-to the dose of 2000 mg/kg and shown better glucose utilization in oral glucose tolerance test. Orally treatment of different doses of MM leaves extract decreased the level of serum glucose, glycated hemoglobin, glucose-6-phosphatase, fructose-1-6-biphosphate and increased the level of plasma insulin, hexokinase. MM treatment decreased liver malondialdehyde but increased the level of superoxide dismutase, catalase and glutathione peroxidase. In oral glucose tolerance test observed increased utilization of glucose. Streptozotocin induced diabetes groups rat treated with different doses of MM leaves extract and glibenclamide significantly increased the body weight. Histopathology analysis on different organ of STZ (streptozotocin) induced diabetic rat show there regenerative effect on the liver, kidney, heart and pancreas. CONCLUSION: The antioxidant, antihyperlipidemic and antidiabetic effect of methanolic extract from Melastoma malabathricum Linn suggests a potential therapeutic treatment to antidiabetic conditions.